Diagnosing the Fine Structure of Electron Energy Within the ECRIT Ion Source - 金逸舟 杨涓 汤明杰 罗立涛 冯冰冰 (Plasma science & technology, 2016)
The ion source of the electron cyclotron resonance ion thruster （ECRIT） extracts ions from its ECR plasma to generate thrust, and has the property of low gas consumption （2 seem, standard-state cubic centimeter per minute） and high durability. Due to the indispensable effects of the primary electron in gas discharge, it is important to experimentally clarify the electron energy structure within the ion source of the ECRIT through analyzing the electron energy distribution function （EEDF） of the plasma inside the thruster. In this article the Langmuir probe diagnosing method was used to diagnose the EEDF, from which the effective electron temperature, plasma density and the electron energy probability function （EEPF） were deduced. The experimental results show that the magnetic field influences the curves of EEDF and EEPF and make the effective plasma parameter nonuniform. The diagnosed electron temperature and density from sample points increased from 4 eV/2 ×10^16 m-3 to 10 eV/4×10^16 m-3 with increasing distances from both the axis and the screen grid of the ion source. Electron temperature and density peaking near the wall coincided with the discharge process. However, a double Maxwellian electron distribution was unexpectedly observed at the position near the axis of the ion source and about 30 mm from the screen grid. Besides, the double Maxwellian electron distribution was more likely to emerge at high power and a low gas flow rate. These phenomena were believed to relate to the arrangements of the gas inlets and the magnetic field where the double Maxwellian electron distribution exits. The results of this research may enhance the understanding of the plasma generation process in the ion source of this type and help to improve its performance.